Sensory Processing Sensitivity as a Predictor of Proactive Work Behavior and a Moderator of the Job Complexity–Proactive Work Behavior Relationship - Schmitt, Antje (Frontiers in Psychology, 2022)
This study investigates the role of sensory processing sensitivity (SPS) as a predictor of employees’ proactive work behavior. SPS is a multidimensional concept that depicts differences in people’s sensory awareness, processing, and reactivity to internal and external influences. Based on research on SPS as grounded in a heightened sensitivity of the behavioral inhibition and activation systems, it was argued that the relationships with task proactivity and personal initiative as indicators of proactive work behavior differ for the three SPS dimensions. Furthermore, based on the person–environment fit perspective, SPS was assumed to moderate the relationship between employees’ job complexity and proactivity. The hypotheses were tested in two two-wave studies (N = 215 and N = 126). Across both studies, ease of excitation (EOE; i.e., the tendency to be easily overwhelmed by changes) was unrelated to proactivity. Low sensory threshold (LST; i.e., unpleasant arousal from external stimuli) was negatively related to personal initiative, but not to task proactivity, only in Study 2. Meanwhile, aesthetic sensitivity (i.e., AES; awareness of and openness to positive stimuli) was positively related to proactivity, but in Study 2, this relationship could only be established for personal initiative. Moreover, job complexity was positively related to proactivity for those employees high but not for those low in AES. EOE and LST did not act as moderators. This study offers evidence of positive behavioral implications among highly sensitive persons when dealing with job complexity. Overall, the study presents an interesting point of departure for the role of SPS in employee proactivity that calls for more research.